Alterations in hepatic mitotic and cell cycle transcriptional networks during the metabolic switch in broiler chicks - Hicks, Julie A.; Pike, Brandon E.; Liu, Hsiao-Ching (Frontiers in Physiology, 2022)
During embryonic life, chicks mainly derive energy from hepatic oxidation of yolk lipids. After hatch, chicks must rely on carbohydrate-rich feed to obtain energy. This requires an abrupt and intensive switch of metabolic processes, particularly in the liver. We recently identified a number of transcriptional and post-transcriptional regulatory networks that work concordantly to tune metabolic processes during the metabolic switch. Here, we used delayed feeding post-hatch (48h) to impede the metabolic switch in broilers. We used RNA-seq to identify hepatic transcriptome differences between late stage embryos (E18) and two-day-old chicks (D2), which were either fed-from-hatch (FED) or not fed (DLY). Between FED and E18, 2430 genes were differentially expressed (fold-change≥ 2; FDR p-value 0.05), of these 1237 were downregulated in FED birds and 1193 were upregulated. Between DLY and E18, 1979 genes were differentially expressed, of these 1043 were downregulated and 936 were upregulated in DLY birds. Between DLY and FED, 880 genes were differentially expressed, of these 543 were downregulated and 337 were upregulated in DLY birds. We found that in addition to disturbances in a number of metabolic pathways, unfed chicks had a widespread suppression of gene networks associated with cell proliferation, cell cycle progression and mitosis. Expression patterns suggest that hepatocytes of delayed-fed birds have abnormal mitosis and increased polyploidization. This suggests that post-hatch feed consumption maintains the rate and integrity of liver growth immediately, which in turn, likely helps facilitate the appropriate programming of hepatic metabolic networks.